Referral with the Ambiguous Syntactic Tools and its Relationship to Text Cohesion and Semantics in the Apology and Praise of Ka’b bin Zuhair for the Prophet (PBUH) - Elryah, Abdellteif Gaafer Abdellteif (Dirasat: Human and Social Sciences, 2023)
Objectives: To study the reference syntactic ambiguous tools in Ka’b bin Zuhair’s apology and praise to the Prophet (PBUH) and to highlight the relationship of these tools with the cohesion and significance of the text. Methods: The methodology of this study was tracking the reference syntactic ambiguous tools in Ka’b bin Zuhair’s apology and praise to the Prophet (PBUH) to reveal the relationship of these tools to the coherence of the text and its significance based on the analysis and linking to the theoretical framework. Results: The results showed that there is a collaboration between the reference syntactic ambiguous tools and their contribution to the cohesion of the text and its meaning. It also showed the prominent role of pronouns in achieving the cohesion of the text and its meaning. It also indicated that demonstrative nouns contribute to the vertical link between the parts of the text and the role relative names play in achieving the cohesion of the text and enriching its meaning. Furthermore, the results showed the important role of demonstrative nouns in extrinsic reference that led to the harmony and consistency of the text. Conclusions: The study found that strong relationships among syntactic ambiguous tools enhance text coherence. Pronouns, particularly, easily contribute to achieving coherence and cohesion. Additionally, the research concluded that text parts are connected both vertically and horizontally, enhancing overall coherence and clarity.